(3EYQGH HYV GdcdeGJ GdZGeVI GdHjGf GdeJcQQI Ydi GdCdSf eY HjGf eYGfjgGs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO agPG JYdjb dWja ai EYQGH HYV GdcdeGJ GdZGeVI GdHjGf GdeJcQQI Ydi GdCdSf eY HjGf eYGfjgG HhLg jRjd GdfbGH def CQGO GdYjGf EYQGH cdeI GdLdGdI dG Edg EdG Gddg s
(3BNQgG (B:s
(3aUd ai MQha JCJi CSeGkA hCaYGdkG fMh eG ef QLd hgd ef NGdb ZjQ Gddg hGddg CYde hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg CLeYjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdfMhs